Microtremor HVSR study of site effects in the urban area of the town of Mytilene, Lesvos (Greece) - Preliminary results. - Bouranta, E.; Vallianatos, F.; Hatzopoulos, N. J.; Papadopoulos, I.; Gaganis, P. (Bulletin of the Geological Society of Greece, 2013)
Mytilene is the capital of Lesvos, the eighth largest island in the Mediterranean Sea and the largest in the North Aegean. The region of North Aegean is a geotectonically complex area, because its geodynamic status is directly affected by the North Anatolian Fault Zone. In the present paper, microtremor data have been analyzed for the city of Mytilene using Nakamura technique of Horizontal to Vertical Spectral Ratio (HVSR) to ascertain the structure in terms of the predominant frequency. 100 microtremor measurements have been performed in the city of Mytilene. At each point of microtremor measurement, the natural frequency and amplification factor have been determined. The predominant frequency varies from 0.4 Hz to 6.6 Hz. The amplification factor in 0.4-8.07 range has been obtained from the HVSR analysis. The results are presented in terms of maps, including the spatial variability of the predominant frequency and developed GIS database. The results of this study make it clear that the characteristics of microtremors depend on the type of soil deposits.